Sejarah dan Perkembangan Penulisan Tafsir Al-Quran di Madura - Ulfatun Hasanah (Al-Fanar: Jurnal Ilmu Al-Qur’an dan Tafsir, 2020)
The attention of Madura’s Scholars to the Qur’an not only ceases to teach the correct and eloquent reading of the Qur’an, but continues to the understanding of the verse content. This is evidenced by the existence of several works in the study of the Qoran that developed in Madura, both in Madurese, Indonesian, and even Arabic. Historically, the genealogy of Tafsir in Madura began with the discovery of the Qoranic translated by Khalil Bangkalan in the 1900s. After Khalil’s era then grow the work of interpretation with a variety of forms and variants, ranging from oral interpretation, interpretation based on certain suras in the Qoran, to a complete interpretation of 30 Juz. This indicates that the development of Qoranic Interpertation in Madura continues to progress from time to time. This paper will explain comprehensively the history and characteristics of the interpretation in each period, starting from the form, method, to the style of interpretation in Madura. In addition, it also explains the behavior of the Madurese people towards their contact with the Qur’an, since the early Islamization era in Madura